Zagnieżdżony algorytm ewolucyjny - Rośczak, Paweł (Embedded Evolutionary Algorithm, 2007)
The article presents the optimization problem of evolutionary algorithms execution parameters. In embedded evolutionary algorithm execution parameters of primary algorithm are optimized by secondary algorithm. It allows to avoid situation where arbitrary choice of algorithm execution parameters delays search process of optimal solution or prevents finding acceptable solution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 232-243